2022
DOI: 10.3390/ijerph19073753
|View full text |Cite
|
Sign up to set email alerts
|

Management Decisions: The Effectiveness and Size of the Emergency Medical Team

Abstract: In Poland, often for economic reasons, the staffing of medical rescue teams is limited to the legally required minimum. This gives rise to problems related to the effectiveness and efficiency of medical rescue teams. A literature review did not find any sources addressing the issue of the verification of the effectiveness of paramedic teams depending on the personnel composition of units. The aim of the study was to analyze the effectiveness of resuscitation depending on the size of the medical rescue team, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“… 14 Several simulation studies demonstrated superior CPR quality (chest compression quality and fraction) in teams larger than two, along with a more efficient achievement of critical CPR endpoints such as rhythm recognition, adrenaline administration, and tracheal intubation. 20 , 21 , 22 No significant difference in the no-flow fraction was observed between teams of two, three, and four paramedic students in one simulated ALS/CPR study. 23 One study comparing team compositions found that teams of two paramedics were more prone to errors and generally slower in most interventions (except for tracheal intubation), compared to paramedic-emergency medical technician (EMT) teams.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“… 14 Several simulation studies demonstrated superior CPR quality (chest compression quality and fraction) in teams larger than two, along with a more efficient achievement of critical CPR endpoints such as rhythm recognition, adrenaline administration, and tracheal intubation. 20 , 21 , 22 No significant difference in the no-flow fraction was observed between teams of two, three, and four paramedic students in one simulated ALS/CPR study. 23 One study comparing team compositions found that teams of two paramedics were more prone to errors and generally slower in most interventions (except for tracheal intubation), compared to paramedic-emergency medical technician (EMT) teams.…”
Section: Resultsmentioning
confidence: 85%
“… Robak (2020) 27 Paramedics ( n = 40) ALS/CPR with pre-filled medication syringes Time to critical interventions The use of pre-filled adrenaline syringes: shorter time to intraosseous access, shorter time to adrenaline. Robakowska (2022) 22 Paramedics ( n = 463) Team size comparison CC quality, time to critical interventions 3-member teams: critical interventions faster, quality of CC comparable. Siebers (2009) 26 EMTs and paramedics ( n = 104) Early TI during ALS/CPR CC interruptions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations